Human development in fragmented societies - Saenz, Karla (Colección de libros electrónicos de ULoyola, 2016)
This book analyzes the complexity of today?s society from an ecumenical perspective. It analyzes the global humanitarian crisis reality and how to approach it from the policies of proximity. Understanding that in order to meet the new society needs, a humane and compassionate approach through sustainable common development is a priority. The authors explain how society has the historical challenge of taking control of its environment and to play a new role as citizens, where the center of human activity returns to be the human being. And through forgiveness, commiseration and peace as an activity, diminish the pain that today, millions of people on the planet suffer from being displaced from their territory, in exodus, without food, without the right to life, health, and to have their own identity and die with dignity. It shows the commitment of the government to adapt itself to this social scenario, showing the ways in which it is possible to respond through policies that meet cooperation criteria, care of the environment and innovative leadership for local development with healthy, happy communities, and with a collective vision of the future.